Pocket E-Li: listening assessments made easy / Norazean Sulaiman, Nurul Nadiah Dewi Faizul Ganapathy and Wan Faizatul Azirah Ismayatim - Sulaiman, Norazean; Faizul Ganapathy, Nurul Nadiah Dewi; Ismayatim, Wan Faizatul Azirah (Akademi Pengajian Bahasa, 2019)
Listening skills should be given more attention as listening takes precedence over anything else when it comes to acquiring a language (Putriani, Sukirlan & Supriyadi, 2013). Even with the expansion of various technology to facilitate teaching and learning of listening skills in class, the assessment conducted to identify students' level of understanding of a certain topic is still not up-to-date and not parallel with the advancement of technology. The current studies show that the use of mobile apps for listening purpose is proven to be effective in reducing students' anxiety (Rahimi & Soleymani, 2015), sustaining students' motivation (Read & Kukulska-Hulme, 2015), and improving students' linguistic competencies (Ramos & Valderruten, 2017). This study is aimed to investigate the students' perceptions on the use of mobile application for listening assessment. 50 Diploma students from various faculties in UiTM Shah Alam were randomly chosen to answer listening comprehension questions via the prototype developed, named Pocket E-Li. Their feedback on the experience of using mobile application prototype for listening assessment is collected via Google Form. The results demonstrate that the majority of the students provided positive response towards the implementation of mobile application for listening assessment. Almost all of the respondents agreed that listening assessment should be conducted via mobile application in the future. It can be concluded that listening assessment via mobile application is beneficial to students since it meets the students' demands and needs which is equivalent with the use of current technology.